2011
DOI: 10.1111/j.1464-5491.2010.03141.x
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of complacency: managing the effects of unrecognized Charcot feet

Abstract: This study reveals that outcomes of stage 0 Charcot neuroarthropathy feet depend on proper recognition and early management. To reduce the rate of future complications for Charcot foot should be the goal of all treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
86
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 17 publications
1
86
0
5
Order By: Relevance
“…1 In a recent series the diagnosis of acute Charcot foot was missed before specialist referral in 19 of 20 patients. 2 In another report, referring clinicians failed to diagnose Charcot foot in 19 of 24 cases seen in a specialist diabetes foot clinic. 3…”
Section: What Is Acute Charcot Foot?mentioning
confidence: 99%
See 1 more Smart Citation
“…1 In a recent series the diagnosis of acute Charcot foot was missed before specialist referral in 19 of 20 patients. 2 In another report, referring clinicians failed to diagnose Charcot foot in 19 of 24 cases seen in a specialist diabetes foot clinic. 3…”
Section: What Is Acute Charcot Foot?mentioning
confidence: 99%
“…2 The misdiagnosis of ankle sprain is particularly common if the patient recalls a history of trivial injury. Standard radiographs may show no abnormalities at this stage, contributing to delays in diagnosis.…”
Section: Why Is Acute Charcot Foot Missed?mentioning
confidence: 99%
“…3 Multiple joints of the foot can be affected by Charcot neuroarthropathy. 11,12 When destruction of the affected joints occurs, the biomechanical properties of the foot are altered in patients who have lost sensory feedback. Patients who continue to ambulate load weight over new bony prominences without pain, precipitating the development and eventual chronicity of an ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In a retrospective series of 22 feet with acute Charcot neuroarthropathy, Wukich et al found that 15 feet progressed to destructive arthropathy, and the midfoot was involved 80 percent of the time. 11 Soft-tissue reconstruction of foot wounds in the setting of Charcot neuroarthropathy is a complex problem. A number of different surgical techniques for the closure of ulcers on the foot affected by Charcot neuroarthropathy have been described.…”
Section: Discussionmentioning
confidence: 99%
“…The response to therapy depends on the stage at which the condition is diagnosed. If the diagnosis is made before significant radiological damage has occurred then the successful treatment is more likely to prevent future joint destruction 8. Oral bisphosphonates9 may also be useful, as well as surgical correction10 in carefully selected cases.…”
Section: Discussionmentioning
confidence: 99%